Asian security for world peace : documents of Delhi and Baghdad conferences on peace and security in Asia - Malaviya, H. D. (Harsh Dev), 1917- (Allied Publishers, 1975)
Speeches and documents of the International Conference against Foreign Military Bases and for a Zone of Peace in the Indian Ocean, New Delhi, 1974, and the Conference of Asian Peace Forces for Peace and Security in Asia, Baghdad, 1975.